2015
DOI: 10.1039/c4ta05501b
|View full text |Cite
|
Sign up to set email alerts
|

Conformal and highly adsorptive metal–organic framework thin films via layer-by-layer growth on ALD-coated fiber mats

Abstract: Fiber@ALD@MOF structures fabricated via ALD and layer-by-layer MOF synthesis show good conformality and high adsorption capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 104 publications
(82 citation statements)
references
References 38 publications
2
80
0
Order By: Relevance
“…It is also important to minimize the volume and weight of the active materials to reduce the burden for end users while maintaining substantial long‐term protection. In contrast, MOF thin films immobilized on functional substrates can simplify the handling and deployment, and are likely to promote MOF applications in CWA detoxification.…”
Section: Figurementioning
confidence: 99%
“…It is also important to minimize the volume and weight of the active materials to reduce the burden for end users while maintaining substantial long‐term protection. In contrast, MOF thin films immobilized on functional substrates can simplify the handling and deployment, and are likely to promote MOF applications in CWA detoxification.…”
Section: Figurementioning
confidence: 99%
“…[10][11][12][13][14][15][16] Among the reported MOF catalysts, MOFs containing Zr-based clusters,i ncluding UiO-type MOFs,N U-1000, MOF-808, and PCN-222/MOF-545, have exhibited exceptional catalytic activity for degrading CWAs and simulants with half-lives as short as 0.5 min. In contrast, MOF thin films immobilized on functional substrates can simplify the handling and deployment, [17,18] and are likely to promote MOF applications in CWAd etoxification. Forexample,the powder form of MOFs is not the ideal configuration for gas filters,p rotective suits and clothing.…”
mentioning
confidence: 99%
“…ALD method was also used to initiate polymer film surface for applying other coating methods. For example, Peng et al [ 84 ] and Zhao et al [ 85 ] recently reported its enabling role to molecular layer deposition (MLD) and layer‐by‐layer (LbL), respectively. MLD and ALD are both based on self‐limiting vapor phase surface reactions that offer unmatchable uniformity and controllability to the surface coating layer.…”
Section: Ald Enabled Film Coating Methodsmentioning
confidence: 99%
“…PP surface activation by ALD of polar and hydrophilic oxide nanolayers like Al 2 O 3 enhances the adsorption of charged layers onto the substrate during the initial period of LbL. Zhao et al [ 85 ] combined ALD and LbL to develop novel metal–organic framework (MOF) thin films as adsorptive gas filters for H 2 S and NH 3 removals. [ 89 ] Since there is no active functional group for MOF nucleation on the surface of PP fibers, full coverage of PP film by a homogeneous Al 2 O 3 nanolayer is critical to the attachment of MOF nucleation seeds onto the fibers during the initial process stage of LbL process.…”
Section: Ald Enabled Film Coating Methodsmentioning
confidence: 99%